Korelasi Kebiasaan Membaca dengan Membaca Pemahaman - Olin Nita; Ineng Naini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between reading habits and students' reading comprehension. The method used is quantitative research through a correlation approach. Sampling was carried out using the theory of Non-Probability Sampling with the Sampling technique. The research instrument used questionnaires and multiple-type objective tests. The study results show that the students' reading habits are categorized as special, with an average score of 80, at the mastery level of 76-85%. Students' reading comprehension results are classified as good, with an average count of 73, which is on a scale of 66-75%. The tcount obtained is 2.36 and ttable 2.056. In conclusion, there is a relationship between reading habits and reading comprehension of students of the Indonesian Language Education study program who take the Reading Skills course at Bung Hatta University. Keywords: Reading Habit, Reading Comprehension